Is so, that's east: |e^(npi i)|<= 1 while the denominator increases without limit.
sinh(z)= (e^(z)- e^(-z))/2i so sinh(npi i)/2= [(e^(n pi i)- e^(n pi i))/2] (1/2i)= sin(n pi) (-i/2) and sin(n pi)= 0 for all n.b) sinh[(npii)/2]
a) I presuming that the dominant term is e, but when I divide by it I get
Is this the right way of doing it? If not can someone point me in the right direction.
b)For this one I had
sinh[(npii)/2]=(e^(npii/2) - e^(-npii/2))
I tired a way using the the triangle inequality followed by the squeeze rule, but that came out wrong, so I dont know where I went wrong.
If anyone could please, please help, I would be very grateful.